Innovative Pedagogies: Enhancing ELT/TESOL Through Technology and Collaboration - Sartini; Ratih, Koesoemo; Fauziati, Endang (Universitas Islam Ahmad Dahlan (UIAD), 2024)
This paper explores the integration of innovative pedagogies in English Language Teaching (ELT) and Teaching English to Speakers of Other Languages (TESOL) through the use of technology and collaborative learning. Employing a qualitative approach, the study captures the experiences of educators and students through in-depth interviews, focus group discussions, and classroom observations. Traditional teaching methodologies often fall short in addressing diverse learner needs and fostering engagement. By leveraging technological advancements such as language learning apps, virtual classrooms, and interactive multimedia tools, in which educators can enhance accessibility, personalize instruction, and increase student interaction. Additionally, collaborative learning strategies, including project-based learning and online discussion forums, cultivate critical thinking, communication, and teamwork skills. This paper examines successful case studies and highlights the benefits and challenges of implementing these approaches. The findings underscore the potential of technology and collaboration to transform language education, offering practical recommendations for educators to adopt these innovative methods effectively.